Roll-printed wrinkled electrode for use in a triboelectric generator. (22nd July 2015) - Hong, Daewoong; Jeong, Jaehwa; Choi, Young-Man
Abstract: Triboelectric energy harvesting is one of the most cost-effective energy harvesting technologies that provides a high output power. The technology converts ambient mechanical energy into electrical energy using triboelectric and electrostatic coupling effects. We sought to enhance the energy harvesting performance in a triboelectric energy harvesting device through the use of a microscopically wrinkled electrode. Wrinkles were created using a simple and rapid roll process involving silver nanoparticle ink and a polydimethylsiloxane roller. The fabricated wrinkled patterns were periodic with an interval of about 7 μ m and a height of about 80 nm. The electrodes were qualitatively evaluated using a precision test rig that aligned two test electrodes in a device such that the devices were perfectly parallel and the electrode areas fully overlapped. The rig accurately controlled the contact force and approach speed, which are critical parameters for power generation. The device output power exceeded the output power obtained from a flat electrode. The quantity of triboelectric charges generated by the wrinkled electrode was 137% of the quantity of charge generated by the flat electrode, indicating that the wrinkled surface enhanced the triboelectric charge generation. For a fixed contact force of 8 N and an approach speed of 11 mm s −1, the maximum powers generated by the flat electrode and the wrinkled electrode were 1.05 μ W and 2.3 μ W, respectively. The output power of the triboelectric energy harvesting device prepared with the wrinkled electrode improved by 120%.